2012
DOI: 10.1177/1350650112463530
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wear of friction material on performance of ultrasonic motor

Abstract: Friction material is one of the key components in an ultrasonic motor. The wear of the material affects the contact friction and output performance of the motor. A method which utilizes the equivalent wear of friction material to simulate the wear during operation is proposed based on the wear characteristics of the ultrasonic motor's contact interface. A relationship between wear and performances of the ultrasonic motor is constructed. The influences of wear on output performance, friction coefficient of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Ko et al 14 studied the speed characteristics of motors with various thicknesses of FMs. Qu et al 15 investigated the influence of FM thickness on the performances of TWUSM and found that the optimized FM thickness is 0.3 mm under the experimental conditions. Wang et al 16 researched the influence of preload on the operational eigenmode and noise of TWUSM.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ko et al 14 studied the speed characteristics of motors with various thicknesses of FMs. Qu et al 15 investigated the influence of FM thickness on the performances of TWUSM and found that the optimized FM thickness is 0.3 mm under the experimental conditions. Wang et al 16 researched the influence of preload on the operational eigenmode and noise of TWUSM.…”
Section: Introductionmentioning
confidence: 98%
“…The life and performance are closely related to the wear of FM. 3–5 The wear of FM is quite slow under ultrasonic vibration, so it is difficult to analyze the characteristics of TWUSM in the whole life of FM which means the process from work beginning to failure. In many researches about contact problems, the FM is usually equivalent to an elasticity layer 68 or a viscoelasticity layer 2,912 which is usually simplified to Kelvin–Voigt model in simulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ishii et al established a method to predict the service life of USMs with a carbon‐fiber‐reinforced polymer as the frictional material. Qu et al investigated the tribological properties of polytetrafluoroethylene (PTFE), phenolic resin, and Ekonol composites in different environments and proposed a method for selecting frictional materials incorporating operation conditions. Ding et al designed polyvinylidene fluoride and potassium titanate whisker reinforced polytetrafluoroethylene (PTW/PTFE) composites and found that such composites could improve the wear performance of USMs.…”
Section: Introductionmentioning
confidence: 99%
“…Ishii et al presented a method to predict the service life of USM using CF‐reinforced polymer as frictional materials, which was verified by actual experimental measurements. Qu and coworkers researched a series of polymer‐based frictional materials, such as polytetrafluoroethylene (PTFE), phenolic resin, and Ekonol composites, and compared their tribological properties under different environments and provided a guidance for selecting frictional materials according to the operating condition. Ding and coworkers prepared poly(vinylidene fluoride) (PVDF) and potassium titanate whisker (PTW)/PTFE composites which could also improve anti‐wear ability.…”
Section: Introductionmentioning
confidence: 99%